Has the “Million-Dollar Cap” Affected CEO Pay? - Rose, Nancy L; Wolfram, Catherine (American Economic Review, 2000)
High and rising executive pay levels over the past two decades have attracted considerable popular and political hostility. As Michael Jensen and Kevin J. Murphy (1990 p. 227) argue, these forces may constrain compensation practices in informal and indirect ways. Our earlier work documents the impact of such indirect political constraints on executive compensation in regulated sectors (Paul Joskow et al., 1993, 1996). This study investigates the political use of the corporate tax code to influence executive-pay decisions more broadly. In particular, we analyze the provision of the Omnibus Budget Reconciliation Act of 1993 (OBRA) that eliminated corporate tax deductibility for compensation in excess of $1 million for the CEO and each of the next four highestpaid executives within a firm. Congressional proponents of this legislation argued that this provision would reduce excessive CEO pay by raising its cost to the corporation. Exemptions for qualified performance-based compensation could have further indirect effects by inducing changes in the structure of executive compensation plans. Given the broad scope for exemptions and the minimal impact that tax deductibility of executive pay typically has on overall corporate profitability, however, the real impact of the tax cap on executive-pay patterns remains an open question. This paper, with Rose and Wolfram (2000), extends analyses by Tod Perry and Marc Zenner (1999) and Brian Hall and Jeffrey Liebman (2000), to provide further evidence on the impact of this legislation on CEO pay.